Mapping perpetrator prosecutions in Latin America - Collins, Cath (International journal of transitional justice, 2013)
This collaborative article examines how two academic institutions and one nongovernmental organization cooperated to map recent trial activity for past human rights violations, applying social science techniques to assist survivors’ and relatives’ groups as well as litigators in making informed strategic choices in their interactions with the formal justice system. The article discusses how methodologically rigorous data collection and data requests to public bodies can be used to advance a proaccountability agenda. The authors show how a range of civil society and state actors have changed justice system outcomes in Argentina, Chile and Peru and highlight some lessons learned about engaged, policy-relevant research.